2022
DOI: 10.1177/09717218221125223
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Technology Transfer, R&D and Innovation: Resolving the Technology–Productivity Conundrum

Abstract: This study aims to empirically investigate the impact of foreign technology transfer and R&D on total factor productivity and labour productivity of Indian firms. The results of production function analysis indicate that foreign technology plays a significant role in output growth. The results of growth the accounting approach also suggest a critical role of foreign technology in the productivity growth of firms. Interestingly, our findings indicate that while R&D does not significantly contribute to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In our method for the re-calculation of performance index points of TDZs (Tables 3 and 4), it would become possible to consider the firm composition with regard to the role of productivity in design and innovative technological research (Table 5) [28]. From the results, it is observed that changing the scalar weights of the indicators also changes the performance index points of TDZs, which may influence the incentives from the government and investments of TDZs in innovative technologies such as intelligent spaces.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our method for the re-calculation of performance index points of TDZs (Tables 3 and 4), it would become possible to consider the firm composition with regard to the role of productivity in design and innovative technological research (Table 5) [28]. From the results, it is observed that changing the scalar weights of the indicators also changes the performance index points of TDZs, which may influence the incentives from the government and investments of TDZs in innovative technologies such as intelligent spaces.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the Ministry ceased including 'exports and composition of firms' as an indicator after 2012 (Table 3). Nevertheless, 'export and firm composition' is commonly used in various countries as an indicator [28] and is regarded as significant in terms of further empirical research, including this indicator and other indicators for the development of sustainable innovation ecosystems. The errors in the numeric values are less than 0.0005.…”
Section: The Evaluation Methods For the Performance Indexes Of The Td...mentioning
confidence: 99%
See 2 more Smart Citations
“…Technology transfer can increase firm productivity (Sharma & Mishra, 2022), promote regional green development (Su & Fan, 2022), promote firm technology upgrading (Bozeman, 2000; Min et al, 2020), and reduce poverty (Rambe & Khaola, 2022; Swinnen & Kuijpers, 2019). When technology transfer occurs, the technological level of firms improves and the leads to competition pattern changes.…”
Section: Introductionmentioning
confidence: 99%